Effects of Tai Chi on Cognition and Fall Risk in Older Adults with Mild Cognitive Impairment: A Randomized Controlled Trial - Somporn Sungkarat (2018)
© 2016, Copyright the Authors Journal compilation © 2016, The American Geriatrics Society Objectives: To examine whether combined center- and home-based Tai Chi training can improve cognitive ability and reduce physiological fall risk in older adults with amnestic mild cognitive impairment (a-MCI). Design: Randomized controlled trial. Setting: Chiang Mai, Thailand. Participants: Adults aged 60 and older who met Petersen's criteria for multiple-domain a-MCI (N = 66). Intervention: Three weeks center-based and 12 weeks home-based Tai Chi (50 minutes per session, 3 times per week). Measurements: Cognitive tests, including Logical Memory (LM) delayed recall, Block Design, Digit Span forward and backward, and Trail-Making Test Part B–A (TMT B–A), and fall risk index using the Physiological Profile Assessment (PPA). Results: At the end of the trial, performance on LM, Block Design, and TMT B–A were significantly better for the Tai Chi group than the control group after adjusting for baseline test performance. The Tai Chi group also had significantly better composite PPA score and PPA parameter scores: knee extension strength, reaction time, postural sway, and lower limb proprioception. Conclusion: Combined center- and home-based Tai Chi training three times per week for 15 weeks significantly improved cognitive function and moderately reduced physiological fall risk in older adults with multiple-domain a-MCI. Tai Chi may be particularly beneficial to older adults with this condition.